The evil corporation master frame: The cases of vaccines and genetic modification. (April 2023) - Silva, Eric O.; Dick, Brian; Flynn, Matthew B.
Employing a qualitative content analysis of online comments made on YouTube and letters to the editor published in US newspapers, we examine the deployment and neutralization of the evil corporation master frame in debates on two distinct biotechnologies, vaccines and genetically modified organisms. This study builds on previous research by outlining three diagnostic components of the evil corporation master frame: dishonesty, greed, and the contamination of authority. It also finds that supporters of vaccines and genetically modified organisms seek to neutralize the evil corporation master frame through aggressive, defensive, endurance, and redemptive framings. This study provides ideational detail for the ways that controversial biotechnology is constructed. The particularly vexing anti-vaccine movement is not dissimilar from other challenges to mainstream science as disparate movements draw on the same master frame. It also demonstrates how defenses of genetically modified organisms and vaccines tend to reify the anti-corporate stigma that sustains challenges to scientific authority.